A Vegetable Oil as Heat Transfer Fluid for Parabolic Trough Collector: Dynamic Performance Analysis under Ouagadougou Climate Conditions - Boubou Bagré; Sié Zacharie Kam; Yomi Woro Gounkaou; Makinta Boukar; Ibrahim Kolawole Muritala; Harouna Sani Dan Nomao; Korsaga Armand; Antoine Beré; Tizane Daho (Materials Proceedings, 2024)
In this study, the thermal performance of the parabolic trough collector (PTC) has been addressed under Ouagadougou climate conditions. Thus, after developing a model, the effect of mass flow on PTC performance showed that the Jatropha curcas oil (JCO) temperature difference increases when the mass flow rate (<semantics><mover accent="true">m˙</mover></semantics>) decreases while the thermal efficiency (<semantics>ηth</semantics>) increases. For <semantics><mover accent="true">m˙</mover></semantics> of 1 kg s−1, a collector length of 46.8 m or collection area of 230 m2 is required to obtain an outlet temperature of 210 °C with an average <semantics>ηth</semantics> of 82.69%. This paper can support the decision for a demonstration plant implementation regarding JCO use in the CSP plant.